Between truth and power : the legal constructions of informational capitalism - Cohen, Julie E. (New York, NY : Oxford University Press, 2019)
This work explores the relationships between legal institutions and political and economic transformation. It argues that as law is enlisted to help produce the profound economic and sociotechnical shifts that have accompanied the emergence of the informational economy, it is changing in fundamental ways.
Also issued in print: 2019.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on September 12, 2019).
Keywords: Internet industry -- Law and legislation -- United States; Trade regulation -- United States